Parental Perspectives on the Postpartum Bonding Experience after Neonatal Intensive Care Unit Transfer to a Referral Hospital - Yui, Yvonne; October, Tessie W. (American Journal of Perinatology, 2020)
Objective The aim of this study is to describe the postpartum bonding experience of parents whose newborns were transferred to a referral hospital while their mothers remained at the delivery hospital.Study Design A total of 18 semi-structured interviews conducted with mothers within 2 weeks of birth were completed. Thematic analysis was performed.Result In total, 72% of mothers were unable to hold their newborns, and mothers spent a median of 15 minutes with their newborn prior to transfer. Thematic analysis revealed five themes: three barriers to bonding (medical, hospital, and family barriers) and two themes of interventions that helped promote bonding (parent and hospital-initiated interventions). Using technology such as bedside cameras, recording of heart beats, and video chatting on rounds were extremely popular.Conclusion Parents identified multiple barriers to maternal–infant bonding and suggested several parent-focused and hospital-focused interventions to enhance bonding. Strategies that address barriers should be used to help parents promote bonding during separation from their newborns.Key Points
Keywords: neonate; transfer; postpartum; bonding; separation